ADDED VALUE AT REGIONAL AGRI-FOOD PRODUCTS IN ARGENTINA "DENOMINATION OF ORIGIN SALAME OF TANDIL" A CASE STUDY OF SOCIAL COOPERATION AND LOCAL DEVELOPMENT - Jatib, María Inés; Bentivegna, Marina; Repetto, Horacio A. (European Scientific Journal, ESJ, 2014)
Geographical Indications and Denominations of Origin are an agrifood strategy, in which the geographical name, and ecological niche – product process (methods of production and local traditional processing) and whose close association comes together to get an original and inimitable product that retains its identity throughout the value chain. This strategy of adding value began to spread in Argentina in the nineties, but legal protection is only achieved at the local level (the national law and its amendments are from 2000 and Regulatory Decree from 2005), since they are not protected at the international level because the MERCOSUR- EU negotiations are still open to discussion. One of the successful cases, the object of this study, is the Denomiation of Origin “Salame of Tandil.” In this paper is presented the advances and setbacks that occurs in Argentina, showing a model of social cooperation and local development, which is the DO Salame of Tandil, and considering the various factors that restrict their commercial development, - presented aspects are discussed in the above - and particularly the human aspects, whose greatest difficulty falls on investments to be made by actors to achieve compliance with quality standards and the effort involved in the different ways of associations required by law. This case is definitly a model of the re-engineering process of agricultural and industrial of Small and Middle enterprises in the regional agri-food business, but has limitations that could be solved by the Council itself and others, that depends on national and international policy strategies.